The Role of Mobile Journalism in Revealing the Violations of the "Israeli Occupation" against Palestinian Journalists – A Survey Study - Asa’d, Huda Othman Musa; Al-Badri, Hani; Oreqat, Ahmad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to investigate the role of smartphone journalism in monitoring Israeli violations against Palestinian journalists, reasons for usage, and associated skills and ethical standards. Methods: Employing media survey methodology, 200 field reporters received questionnaires, and 10 journalists participated in in-depth interviews. The study, grounded in Media Richness Theory, spanned from 24/2/2023 to 24/4/2023. Results: The prominent reasons for Palestinian reporters' use of smartphones in covering Israeli violations included assisting in covering urgent and unexpected news through live broadcasting (mean score: 4.64) and easing the transition with heavy equipment (mean score: 4.62). Key ethical standards for smartphone journalism included adherence to professional standards such as accuracy and objectivity (mean score: 4.58), followed by reliance on credible sources (mean score: 4.57). The study recommended enhancing field reporters' skills in smartphone journalism through training to keep up with digital advancements and prioritize digital security during documentation of violations. Conclusions: Smartphone journalism plays a significant role in monitoring Israeli violations against Palestinian journalists. Palestinian journalists utilize smartphones for ease, cost-effectiveness, and documenting events, including violations they face, showcasing advanced skills in photography, editing, writing, and dissemination.